TUGAS DAN TANGGUNG JAWAB PUBLIC AREA DI DEPARTMENT HOUSEKEEPING PADA GRAND JATRA HOTEL PEKANBARU - Rohani Seventina Debora Sitanggang; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The role of the public area is very important in hotel operations, the public area is part of the housekeeping which handles the cleanliness and tidiness of the public areas of the hotel, the cleanliness and tidiness of the hotel which are visited by many guests. All kinds of cleaning matters in public areas are carried out by the public area, in order to give a clean and comfortable impression to the hotel environment and make guests who come have a good impression of the hotel. The purpose of this writing is expected to increase guest comfort when entering the Grand Jatra Hotel Pekanbaru area. The method used by the author is a descriptive method which is used to describe or describe the data as it is, which is done simply about the problems and existing conditions with the intention of providing an overview of the object of research. The results of this study stated that there were several procedures that were not carried out by public area attendent staff, so that work results were not optimal because they were not in accordance with standard operating procedures (SOP). Based on these results, the author's suggestion can be conveyed, public area staff must pay attention to the work time and rest time that has been set, so that the duties and responsibilities can be carried out according to standard operating procedures (SOP). Cleaning equipment should never be left behind after work, because it affects the operations in the hotel. Keywords : Duties, responsibilities, public area, grand jatra hotel Pekanbaru, housekeeping department